Seleção de tecnologias de tratamento de esgoto utilizando análise multicritério - Freitas, Elaine Cristina Brás de (2020)
Among the main causes of pollution of water bodies is the discharge of sewage without any type of treatment. To reduce this type of pollution, it is necessary to implement efficient sewage treatment systems, whether they are the responsibility of public service providers or the respective generators. The choice of sewage treatment technologies is a complex process, as they involve both quantitative and qualitative variables. Thus, to achieve the objective defined in this work, which is the selection of sewage treatment technologies using multicriteria analysis applicable in municipalities in the State of Goiás that do not have a sewage system, the Electre I method was defined, to select from among 37 sewage treatment technologies most used in Brazil, a set composed of the best technology options. For this, three scenarios were defined, and 16 criteria with technical, economic, social and environmental characteristics for scenario 1, 10 criteria for scenario 2 and 8 criteria for scenario 3. The application of the method was adequate for the selection of technologies sewage treatment. The selection for scenario 1 indicated a set consisting of 2 alternatives (anaerobic lagoon + optional lagoon + maturation pond and slow infiltration); for scenario 2 a set consisting of 5 alternatives (septic tanks, optional pond, optional aerated pond, slow infiltration and UASB reactor) and for scenario 3 a set with 3 alternatives (septic tanks, optional aerated pond and UASB reactor).